ANALYZING TEACHERS’ STRATEGIES IN TEACHING VOCABULARY OF JUNIOR HIGH SCHOOLS AT KECAMATAN - Moh Farham; Ferry Rita; Mashuri Mashuri (e-Journal of ELTS (English Language Teaching Society), 2021)
The purpose of this research was to investigate the teachers’ strategies in teaching vocabulary to the second grade students of SMP Negeri 1, SMP Negeri 2, and SMP Satap Negeri 1 Kasimbar. The design used was descriptive qualitative. The research subjects were three English teachers teaching vocabulary in three different schools. In collecting the data, the researcher interviewed the three teachers and analyzed the the interviewed results. The results of this research indicate that the strategies used by the three English teachers were different Teacher one used a dialogue strategy, teacher two used showing picture strategy, and teacher three used a question and answer strategy. each of these three strategies has advantages in improving students' vocabulary skills. In addition, the problems faced by the three English teachers in teaching vocabulary to the students in the second grade of junior high schools at Kecamatan Kasimbar also have many factors such as Unstable internet network, lack of student interest in learning English vocabulary, likes to annoy friends in class, most students do not bring a dictionary to school and pronunciation errors. to solve the problems the three teachers Always evaluate the learning given, avoid giving very long assignments, invite students to actively participate, teach note-taking, personal approach, and form groups of students in learning.